Scenarios of the innovative development of education in the context of the Russian economy’s modernization: entrepreneurial universities vs. high-tech universities - Dvoretskaya, Vera V.; Antonova, Irina S.; Semenova, Galina N.; Belkina, Elena N. (Frontiers in Education, 2023)
The article is aimed at identifying the scenarios of the innovative development of education in the context of the Russian economy’s modernization through the opposition of entrepreneurial universities and high-tech universities. The authors conduct a system econometric analysis. The scenario analysis showed that the strategic prospects (optimistic, long-term scenario) of the innovative development of education to support the modernization of the Russian economy through the optimization of universities' activities require the upgrading of equipment by 982.51% for increasing the research activities to 10,269.44% (compared to the threshold), which will bring Russian universities to the 1st place in the QS ranking. In the medium-term period, the share of modern (less than 5 years old) equipment in Russian universities should tend to be 90%. As it is shown by a probable and promising scenario, this will improve the position of the Russian universities in the QS ranking by 6.17%. It is proved that only high-tech universities contribute to the innovative development of education in the context of the Russian economy’s modernization. Therefore, the reduction of state funding of higher education and science makes no sense in Russia, as well as the development of entrepreneurial universities. Instead, the focus should be on the upgrading of university equipment.